Survey Kondisi Fisik Siswa Pencak Silat PSHT Kabupaten Gorontalo - Kasim Al Kadri (Gorontalo State University, 2026)
Background: This study is motivated by the lack of empirical data on the physical condition profile of pencak silat students as a basis for developing structured training programs, particularly at the regional level. Objective: This study aims to analyze the physical condition of Pencak Silat PSHT students in Gorontalo Regency. Method: A quantitative descriptive method with a survey approach was used. The subjects were 30 male students aged 15–18 years selected through purposive sampling. Instruments included the Multistage Fitness Test (bleep test) for cardiovascular endurance and the push-up test for arm muscle strength. Data were analyzed using descriptive statistics in percentages. Results: The findings showed that 60% of students were in the good category, 30% moderate, and 10% poor for endurance. For arm strength, 50% were good, 40% moderate, and 10% poor. Conclusion and Implications: Overall, the physical condition of PSHT students is generally in the good category, with some individual variation. These results can serve as a basis for designing structured and data-driven training programs.